2019
DOI: 10.3332/ecancer.2019.978
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of human papilloma virus and cervical cancer prevention among Cypriot female healthcare workers

Abstract: Background: Cervical cancer incidence varies around the world with the highest rates in Eastern Africa and the lowest rates in Western Asia. In Cyprus, a small Mediterranean island, cervical cancer incidence was 6.4 per 100,000 in 2013. HPV is an established risk factor for cervical cancer with HPV-16 and HPV-18 being the most common carcinogenic strains. Cervical cancer is preventable through primary (HPV vaccination) and secondary (Pap and HPV tests) prevention. These prevention methods should be promoted, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“… 44 Finally, while 34.9% of nurses not vaccinated against HPV in Turkey stated not being at risk of HPV, 45 70%-83.5% of HCPs from Greece and Cyprus stated they would accept HPV vaccination to protect themselves against HPV infection or cervical cancer. 46 , 47 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 44 Finally, while 34.9% of nurses not vaccinated against HPV in Turkey stated not being at risk of HPV, 45 70%-83.5% of HCPs from Greece and Cyprus stated they would accept HPV vaccination to protect themselves against HPV infection or cervical cancer. 46 , 47 …”
Section: Resultsmentioning
confidence: 99%
“…Confidence in HPV vaccine effectiveness was high among Italian HCPs (83.5–92.6%). 81 , 82 However, doubts about the effectiveness of HPV vaccination and the prevention of cervical cancer were raised by 25% of HCPs in Turkey , 73 16.7–23.5% of GPs in France , 75 , 83 14.28% of HCPs who would refuse the vaccine in Cyprus , 46 and 65.7% of HCPs from Spain . 52 Such doubts were also provided as a reason for doubting or not recommending HPV vaccination by 2.3–5.3% of HCPs in Turkey 72 and by HCPs in the UK , 84 Greece 85 and France .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study conducted among health workers in Cyprus (a developed country), statistical analysis revealed that the population under the investigation had good knowledge about HPV. Thus, 88.5% of 200 women indicated to have good knowledge about HPV (Christodoulou et al, 2019). In contrast, another study conducted in Gondar town, Ethiopia (a developing country), revealed that >80% of 770 women indicated not to have any knowledge about HPV as one of the germane risk factors of CC (Mengesha et al, 2020).…”
Section: Inadequate Knowledge About Hpv and The Formation Of CCmentioning
confidence: 94%
“…Different screening methods and technologies make up more than half of the patients in the middle and advanced stages when they visit the clinic in different regions. e cure rate is relatively high for early cervical cancer [2,4,5]. erefore, it is important to search for the cause and early diagnosis of cervical cancer and find new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%